Insights from letter position dyslexia on morphological decomposition in reading - Friedmann, Naama; Gvion, Aviah; Nisim, Roni (Frontiers in Human Neuroscience, 2015)
We explored morphological decomposition in reading, the locus in the reading process in which it takes place and its nature, comparing different types of morphemes. We assessed these questions through the analysis of letter position errors in readers with letter position dyslexia(LPD). LPD is a selective impairment to letter position encoding in the early stage of word reading, which results in letter migrations (cloud-could). We used the fact that migrations in LPD occur mainly in word-interior letters, whereas exterior letters rarely migrate.The rationale was that if morphological decomposition occurs prior to letter position encoding and strips off affixes, word-interior letters adjacent to an affix (signs-signs) would become exterior following affix-stripping and hence exhibit fewer migrations. We tested 11 Hebrew readers with developmental LPD and 1 with acquired LPD in 6 experiments of reading aloud, lexical decision, and comprehension, at the single word and sentence levels. We examined migrations next to inflectional,derivational,or bound function morphemes compared with exterior letters. Root letters adjacent to inflectional and derivational morphemes were treated like middle letters, and migrated frequently, whereas root letters adjacent to bound function morphemes patterned with exterior letters, and almost never migrated. Given that LPD is a pre-lexical deficit, these results indicate that morphological decomposition takes place in an early, pre-lexical stage. Morphologically complex nonwords showed the same pattern, indicating that this decomposition is structurally, rather than lexically, driven. We suggest that letter position encoding takes place before morphological analysis, but in some cases, as with bound function morphemes, the complex word is re-analyzed as two separate words. In this reanalysis, letter positions in each constituent word are encoded separately,and hence the exterior letters of the root are treated as exterior and do not migrate